Primary Mucinous Tumors of the Ovary: An Interobserver Reproducibility and Detailed Molecular Study Reveals Significant Overlap Between Diagnostic Categories - Dundr, Pavel; Bártů, Michaela; Bosse, Tjalling; Bui, Quang Hiep; Cibula, David; Drozenová, Jana; Fabian, Pavel; Fadare, Oluwole; Hausnerová, Jitka; Hojný, Jan; Hájková, Nikola; Jakša, Radek; et al. (Modern pathology, 2023)
Primary ovarian mucinous tumors represent a heterogeneous group of neoplasms, and their diagnosis may be challenging. We analyzed 124 primary ovarian mucinous tumors originally diagnosed as mucinous borderline tumors (MBTs) or mucinous carcinomas (MCs), with an emphasis on interobserver diagnostic agreement and the potential for diagnostic support by molecular profiling using a next-generation sequencing targeted panel of 727 DNA and 147 RNA genes. Fourteen experienced pathologists independently assigned a diagnosis from preset options, based on a review of a single digitized slide from each tumor. After excluding 1 outlier participant, there was a moderate agreement in diagnosing the 124 cases when divided into 3 categories (κ = 0.524, for mucinous cystadenoma vs MBT vs MC). A perfect agreement for the distinction between mucinous cystadenoma/MBT as a combined category and MC was found in only 36.3% of the cases. Differentiating between MBTs and MCs with expansile invasion was particularly problematic. After a reclassification of the tumors into near-consensus diagnostic categories on the basis of the initial participant results, a comparison of molecular findings between the MBT and MC groups did not show major and unequivocal differences between MBTs and MCs or between MCs with expansile vs infiltrative pattern of invasion. In contrast, HER2 overexpression or amplification was found only in 5.3% of MBTs and in 35.3% of all MCs and in 45% of MCs with expansile invasion. Overall, HER2 alterations, including mutations, were found in 42.2% of MCs. KRAS mutations were found in 65.5% and PIK3CA mutations in 6% of MCs. In summary, although the diagnostic criteria are well-described, diagnostic agreement among our large group of experienced gynecologic pathologists was only moderate. Diagnostic categories showed a molecular overlap. Nonetheless, molecular profiling may prove to be therapeutically beneficial in advanced-stage, recurrent, or metastatic MCs.
Keywords: nádory cystické, mucinózní a serózní; borderline; Humans; diagnostic agreement; Female; nádory vaječníků; Ovarian Neoplasms; lidé; Adenocarcinoma, Mucinous; reprodukovatelnost výsledků; Neoplasms, Cystic, Mucinous, and Serous; therapeutic targets; Cystadenoma, Mucinous; ovary; ženské pohlaví; Reproducibility of Results; next-generation sequencing; mucinózní adenokarcinom; mucinózní cystadenom; mucinous tumors